The Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet is associated with physical function and grip strength in older men and women. Issue 3 (12th October 2021) - Talegawkar, Sameera A; Jin, Yichen; Simonsick, Eleanor M; Tucker, Katherine L; Ferrucci, Luigi; Tanaka, Toshiko
ABSTRACT: Background: Diet quality may be protective of physical function and muscle strength during aging. Objectives: We aimed to investigate associations of the Mediterranean-Dietary Approaches to Stop Hypertension (DASH) Intervention for Neurodegenerative Delay (MIND) diet with physical function and grip strength. Methods: Data were obtained from men and women in the Baltimore Longitudinal Study of Aging (mean ± SD age: 68 ± 14 y at first diet visit; n = 1358). Diet was assessed by FFQ. MIND diet score was calculated from 15 food groups, with a higher score indicating better diet quality; tertile categories of averaged MIND score across visits were used. Physical function was assessed using the Short Physical Performance Battery (SPPB), with a score < 10 indicative of impaired function, and the Health, Aging and Body Composition Physical Performance Battery (HABCPPB). The highest value of grip strength over 3 trials was used. Multivariable logistic and linear mixed-effects models were examined with repeated measurements of physical function and grip strength, respectively. Results: MIND score was inversely associated with physical function impairment (per 1-point increment: OR: 0.81; 95% CI: 0.71, 0.93; P < 0.01), and with each SPPB component, over a median 6 y of follow-up. Participants in the highest compared with the lowest tertile of MIND diet score had 57% lower odds of functional impairment (OR: 0.43; 95% CI: 0.25, 0.73; P < 0.01), and slower decline by the HABCPPB. Men and women in the highest compared with the lowest tertiles of MIND score had 1.86-kg (95% CI: 0.33, 3.40 kg; P < 0.05) and 1.24-kg (95% CI: 0.04, 2.45 kg; P < 0.05) greater grip strength, respectively. Conclusions: Adherence to the MIND dietary pattern was associated with lower odds of physical function impairment and decline, and with better muscle strength, indicating that the MIND dietary pattern may be protective of physical functional health in older adults.